Records of Brown spot needle blight related to Lecanosticta acicola in the Czech Republic - Libor JANKOVSKÝ; Dagmar PALOVČÍKOVÁ; Miloň DVOŘÁK; Michal TOMŠOVSKÝ (Plant Protection Science, 2009)
There are two records of brown spot needle blight caused by L. acicola in the Czech Republic up to date. Disease was first reported on June 2007 in National Nature Reserve (NNR) Červená Blata, South Bohemia. A more recent discovery of L. acicola took place on August 2008 in the NNR Borkovická Blata. The disease was observed on 10-60 year old Pinus rotundata. Both locations with infected trees are situated inside nature conservation sites under strict protection regimes that are located approximately 50 km apart. In both sites, L. acicola occurred simultaneously with Dothistroma septospora, the red band needle blight causal agent on Scots pine (Pinus sylvestris), bog pine (P. rotundata) and their hybrid (P. × digenea). However, infections of both diseases on the same tree have not yet been observed.